The many roots of medieval logic : the aristotelian and the non-aristotelian traditions : special offprint of Vivarium 45, 2-3 (2007) - Marenbon, John (Brill, 2007)
Medieval logic is usually divided into the branches that derived from Aristotle's organon - the 'logica vetus' and 'logica nova', and those invented in the Middle Ages, the 'logica modernorum'.